Detecting Vessels in exclusive economic zone (EEZ) of the Republic of Cyprus using Sentinel-1 - Kalogirou, Eleftheria; Melillos, George; Makri, Despina; Hadjimitsis, Diofantos G. (My University, 2023)
Maritime surveillance is critical for threat prevention, national security, and safety maintenance. Maritime traffic involves the worldwide navigation of millions of vessels. Satellite missions like Sentinel-1 made it possible to collect systematic data for vessel tracking. Using the Copernicus Open Access Hub service, it is now feasible to access satellite data in fully automated and near real-time mode and deliver vessel information through a web portal interface. This paper aims to detect vessels in exclusive economic zone (EEZ) of the Republic of Cyprus, Southwest of Cyprus using freely available Sentinel- 1 SAR imagery data. Comparison of results obtained using Sentinel Application Platform (SNAP) and Arc GIS Pro - Deep Learning. The preliminary results show that both tools can be used to ship detection and give satisfactory results.
Keywords: Arc GIS Pro; Cyprus; Detect ships Using Deep Learning; Maritime safety; SNAP